THE COMMONALITY OF EDUCATION AND TRAINING AS A FACTOR OF DEVELOPMENT (World Bulletin of Social Sciences, 2023)
In the course of reforms, the issue of education and some issues of modern pedagogic technologies applied to the process of the education lesson will be discussed in this article. Also, attention is paid to the possibilities of teaching the science of education, and the commonality of education and personal development is analyzed from today's point of view.